CREATIVE DANCE FORM OF OLAN-OLANG FOR LEARNING DANCE AT SMP N 1 DAYUN SIAK DISTRICT RIAU PROVINCE WAHYUNING TIYAS - Wahyuning Tyas (Journal of Dance and Dance Education Studies, 2022)
Olang-olang dance is a traditional Malay dance Riau who comes from one of the deepest tribes, the Sakai tribe in Riau Province, precisely in Minas District, Siak Regency. As the name suggests, Olang means Eagle in the Malay dialect. Olang-olang dance used to be used by the Sakai tribe in treatment rituals, when one of the Sakai tribe members was sick, this ritual was held in addition to the existing traditional treatment. The Olang-olang dance depicts the Eagle bird that can fly high into the sky, as a symbol of an intermediary or prayer leader to God. This research describes the creation of olang-olang dance movements used for learning dance art in Junior High School. The method used is qualitative ethnochoreology which refers to the forms of ollang-olang dance movements. Olang-olang dance creations can be used for cultural art teaching materials, especially dance art. The movements in this Olang-Olang dance creation have been standardized to make it easier for students to memorize dance moves. the costume worn on the olang-olang creation is a gold and black nuanced costume that symbolizes luxury, grandeur, and courage.